2021
DOI: 10.3390/app11052404
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Imaging to Unravel the Pathomechanisms Associated with Epileptic Seizures: A Review

Abstract: Despite extensive research, the exact pathomechanisms associated with epileptic seizure formation and propagation have not been elucidated completely. Two-photon imaging (2PI) is a fluorescence-based microscopy technique that, over the years, has been used to evaluate pathomechanisms associated with epileptic seizures and epilepsy. Here, we review previous applications of 2PI in epilepsy. A systematic search was performed in multiple literature databases. We identified 38 publications that applied 2PI in epile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 96 publications
(214 reference statements)
0
4
0
Order By: Relevance
“…On the luminal side of the endothelium, the glycocalyx contributes to the barrier function of the BBB (Figure 1). Using two-photon microscopy, several studies have shown that the glycocalyx acts as a barrier for large molecules (Kutuzov et al, 2018;Khan et al, 2021). The glycocalyx also functions as an electrostatic barrier to plasma proteins due to its negative charge carried by core proteins like hyaluronan, thereby repelling negatively charged cells and preventing them from binding the endothelium (Iba, 2016).…”
Section: Glycocalyx and The Blood-brain Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…On the luminal side of the endothelium, the glycocalyx contributes to the barrier function of the BBB (Figure 1). Using two-photon microscopy, several studies have shown that the glycocalyx acts as a barrier for large molecules (Kutuzov et al, 2018;Khan et al, 2021). The glycocalyx also functions as an electrostatic barrier to plasma proteins due to its negative charge carried by core proteins like hyaluronan, thereby repelling negatively charged cells and preventing them from binding the endothelium (Iba, 2016).…”
Section: Glycocalyx and The Blood-brain Barriermentioning
confidence: 99%
“…However, these techniques are nevertheless limited by the frailty of the glycocalyx in ex-vivo conditions (Reitsma et al, 2007;Haeren et al, 2016). Recent advances in handheld multi-photon microscopy probes could potentially provide a novel in vivo technique to evaluate the glycocalyx (Khan et al, 2021).…”
Section: Techniques For Assessing the Cerebrovascular Glycocalyxmentioning
confidence: 99%
“…The endothelial glycocalyx is a mechanosensor that modulates vascular response to mechanical forces such as shear stress from flowing blood; transduces the force to a biochemical response to maintain vascular tone; and plays a role in preventing coagulation, characteristics that facilitate regulation of CBF. The glycocalyx, by virtue of being a physical electrostatic barrier (due to negative charges on components like HA), prevents plasma proteins and negatively charged cells from attaching to the endothelium, thus averting perturbances in blood flow [29,54,55]. There is emerging evidence that components of the glycocalyx (HS and SD-1) bind with anticoagulant molecules [19,56] that trigger multistep processes which eventually inhibit platelet aggregation and cause relaxation of smooth muscles and vasodilation [57].…”
Section: Discussionmentioning
confidence: 99%
“…Further histological vascular density analysis of thicker slices (30–50 µm) might provide this result, preferably using 3 D visualization such as two-photon microscopy imaging. 72 …”
Section: Discussionmentioning
confidence: 99%